Altered tolbutamide pharmacokinetics by a decrease in hepatic expression of CYP2C6/11 in rats pretreated with 5-fluorouracil. (2nd January 2018) - Fukuno, Shuhei; Nagai, Katsuhito; Kasahara, Keita; Mizobata, Yuki; Omotani, Sachiko; Hatsuda, Yasutoshi; Myotoku, Michiaki; Konishi, Hiroki
Abstract: 1. We investigated the change in the pharmacokinetic profile of tolbutamide (TB), a substrate for CYP2C6/11, 4 days after single administration of 5-fluorouracil (5-FU), and the hepatic gene expression and activity of CYP2C6/11 were also examined in 5-FU-pretreated rats. 2. Regarding the pharmacokinetic parameters of the 5-FU group, the area under the curve (AUC) was significantly increased, and correspondingly, the elimination rate constant at the terminal phase ( k e ) was significantly decreased without significant change in the volume of distribution at the steady state (Vdss ). 3. The metabolic production of 4-hydroxylated TB in hepatic microsomes was significantly reduced by the administration of 5-FU. 4. The expression level of mRNAs for hepatic CYP2C6 and CYP2C11 was significantly lower than in the control group when the rats were pretreated with 5-FU. 5. These results demonstrated that the pharmacokinetic profile of TB was altered by the treatment with 5-FU through a metabolic process, which may be responsible for the decreased CYP2C6/11 expression at mRNA levels.